Inter-goal conflict and facilitation as predictors of adherence to dieting goals: an ecological momentary assessment study. Issue 6 (2nd June 2020) - Elliston, Katherine G.; Schüz, Benjamin; Ferguson, Stuart G.
Abstract: Objectives: To examine dieting goals within a system of individual goals, and the patterns by personally-relevant goals might interfere or facilitate each other. Design: 94 dieters completed an assessment of goals using Little's personal project analysis. Participants identified 7 goals; one of which was pre-defined as adhering to diet. Over the beginning 14 days of their diet, participants completed an Ecological Momentary Assessment study recording their food intake in real-time. Every evening, participants reported their goal engagement and which goals conflicted or facilitated with each other. Main outcome measures/results: Over the study duration, 1452 days of food intake and goal conflict/facilitation were recorded. Participants completed an average of 1.54 ( SD  = 0.85) snacks, an average of 0.94 ( SD  = 1.81) goal conflicts, and 4.16 ( SD  = 4.70) goal facilitations per day. Inter-goal conflict was associated with a significant but small improvement on individuals' mood, but was not associated with daily dietary intake or long-term weight-loss. Similarly, inter-goal facilitation was not associated with daily dietary intake or long-term weight-loss. Daily food intake was a significant predictor of long-term weight-loss. Conclusions: The results of this study suggest the impact of inter-goal conflict and facilitation on dieting is not via overall snack or food consumption.